Biodegradable bilayer hydrogel membranes loaded with bazedoxifene attenuate blood–spinal cord barrier disruption via the NF-κB pathway after acute spinal cord injury. (15th March 2023) - Xin, Wang; Baokun, Zhang; Zhiheng, Chen; Qiang, Shi; Erzhu, Yang; Jianguang, Xu; Xiaofeng, Lian
Abstract: After spinal cord injury (SCI), blood–spinal cord barrier (BSCB) disruption and hemorrhage lead to blood cell infiltration and progressive secondary injuries. Therefore, early restoration of the BSCB represents a key step in the treatment of SCI. Bazedoxifene (BZA), a third-generation estrogen receptor modulator, has recently been reported to inhibit inflammation and alleviate blood–brain barrier disruption caused by traumatic brain injury, attracting great interest in the field of central nervous system injury and repair. However, whether BZA can attenuate BSCB disruption and contribute to SCI repair remains unknown. Here, we developed a new type of biomaterial carrier and constructed a BZA-loaded HSPT (hyaluronic acid (HA), sodium alginate (SA), polyvinyl alcohol (PVA), tetramethylpropane (TPA) material construction) (HSPT@Be) system to effectively deliver BZA to the site of SCI. We found that HSPT@Be could significantly reduce inflammation in the spinal cord in SCI rats and attenuate BSCB disruption by providing covering scaffold, inhibiting oxidative stress, and upregulating tight junction proteins, which was mediated by regulation of the NF-κB/MMP signaling pathway. Importantly, functional assessment showed the evident improvement of behavioral functions in the HSPT@Be-treated SCI rats. These results indicated that HSPT@Be can attenuate BSCB disruption via the NF-κB pathway after SCI, shedding light on its potential therapeutic benefit for SCI. Statement of significance: After spinal cord injury, blood–spinal cord barrier disruption and hemorrhage lead to blood cell infiltration and progressive secondary injuries. Bazedoxifene has recently been reported to inhibit inflammation and alleviate blood–brain barrier disruption caused by traumatic brain injury. However, whether BZA can attenuate BSCB disruption and contribute to SCI repair remains unknown. In this study, we developed a new type of biomaterial carrier and constructed a bazedoxifene-loaded HSPT (HSPT@Be) system to efficiently treat SCI. HSPT@Be could provide protective coverage, inhibit oxidative stress, and upregulate tight junction proteins through NF-κB/MMP pathway both in vivo and in vitro, therefore attenuating BSCB disruption. Our study fills the application gap of biomaterials in BSCB restoration. Graphical abstract: Image, graphical abstract